PENGARUH MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA KARYAWAN DINAS PERTANIAN DAN KEHUTANAN KABUPATEN REMBANG) - Mochamad Setiarta, 1242020069 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study to determine the effect of motivationand organizational climate on performance mediated by the job satisfactionDinas Pertanian dan Kehutanan Kabupaten Rembang. This research was conducted with a sensus method and implemented in Dinas Pertanian dan Kehutanan Kabupaten Rembang. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. Tested the validity of data collected by viewing at the magnitude of the KMO values ââabove 0.5 and the loading factors above 0.4 could be declared valid. The results demonstrate the validity of the KMO test for motivationis 0.871, KMO test for organizational climateis0.909.KMO test for job satisfactionis 0.793 and KMO test for the performance is 0.841. It can be said that all variables declared valid. Its reliability test showed the 0.895 formotivation, 0.949 for organizational climate, 0,943for job satisfaction and 0.933 for performance. These show that all variables are reliable. From the analysis and discussion show that a significant positive influence motivation on job satisfaction, significantly positive effect of organizational climate on job satisfaction, motivation is a significant positive effect on performance, organizational climate significantly positive effect on performance and job satisfaction significantly positive effect on performance. Strong influence of motivation is mediated by job satisfaction to the performance compared directly influence toward the peformance. Moreover of Organizational climate has strong influence mediated by job satisfaction to the performance compared directly influence toward the performance. Keywords: Motivation, Organizational Climate, Job satisfaction and Performance.